Transformation Through Transformative Education: From an Egg to a New Butterfly - Gurung, Sikha (Journal of Education and Research, 2017)
This reflective note is a response to the first international Conference on Transformative Education Research and Sustainable Development that took place in Dhulikhel, Nepal, in October 2016. In this reflective note, I begin by pondering on what makes a novice academic creative and transformative. Then, I deal with the conference atmosphere, contemplate how it connects close to my heart, and finally conclude with my realisation of transformation inside. I particularly reflect on my experiences of being a volunteer to help the scholars from various parts of the world; a rapporteur to witness various talk presentations and report on them; and a participant to attend and learn from some exemplary reports and presentations – all centred at transformative education.